Towards preserving Transylvanian fortified churches in virtual reality - Duguleană Mihai; Postelnicu Cristian Cezar (Springer, 2018)
A fortified church is a building which has a religious meaning, but also played a defensive role in times of war. Many fortified churches from countries such as Romania, Slovenia, Switzerland, Poland, France, Denmark, Portugal, Germany or Belarus featured thick walls and high battlements and embrasures. However, Middle Age fortified churches are different from castles and fortresses because they were designed to protect small communities. Transylvania hosts the highest number of fortified churches from Europe. In the medieval ages, more than 300 churches were built by the inhabitants of this area. This was the direct result of the constant invasions from the Ottomans and other nomad populations such as Tatars. Many of these edifices date since the 13th century, but some are in an advanced state of degradation, caused mainly by poor preservation measures and lack of interest from the local authorities. This paper introduces a system which aims to increase the awareness about the fortified churches from a small area of Transylvania called “Țara Bârsei”. Our focus is on the visual preservation of several of these monuments through the technique of photogrammetry, as well as the implementation of a stand which would attract the potential tourists. The key idea of our study is to influence them to visit several churches by placing next to each other in Virtual Reality both mainstream and low-profile objectives. We assess users’ opinion about a holographic stand commanded by a mobile application which includes the 3D models, pictures and a short description of the fortified churches based on a modified HARUS questionnaire. Results show increased interest, directly resulted from the visualization technology.
Keywords: Transylvanian fortified churches; cultural heritage; preservation